Soybean Tempeh: Effect of Yeast Concentration and Fermentation Duration on Organoleptic Test as a Learning Resource - Mufida; Tri Santoso; Sri H. V. Pulukambang; Dewi S. Ahmar (Universitas Tadulako, 2025)
Tempeh is a traditional Indonesian fermented food known for its high nutritional value. This study sought to assess the impact of yeast concentration and fermentation length on moisture content, protein content, and organoleptic evaluation of yellow soybean tempeh sourced from Tojo Una-Una, Poso, and Palu. The research included a 3 × 3 factorial design incorporating yeast concentrations of 1, 2, and 3 grams, alongside fermentation durations of 30, 48, and 72 hours. The moisture content was assessed using the gravimetric method, the protein content was determined via the Kjeldahl method, and 20 panelists performed an organoleptic evaluation. The findings indicated that the moisture content of tempeh generally rose with prolonged fermentation time and elevated yeast concentration. The maximum moisture content, 63.22%, was observed in tempeh from Tojo Una-Una, which used 2 grams of yeast and had a fermentation duration of 72 hours. The minimum value, 50.18%, was also from Tojo Una-Una with 1 gram of yeast and 30 hours of fermentation. Protein levels peaked at 48 hours of fermentation with 3 grams of yeast, reaching a maximum of 26.88% in the Palu area. In contrast, the minimum was recorded at 18.55% in tempeh from Tojo Una-Una with 2 grams of yeast and 30 hours of fermentation. The organoleptic test results indicated that panelists favored Poso tempeh in terms of flavor, aroma, and texture. The concentration of yeast and the time of fermentation influence the moisture content, protein content, and organoleptic quality of tempeh. The methodologies and findings of this study serve as a resource for chemistry education in the format of LKPD.